BETWEEN DEMOCRACY AND DICTATORSHIP - HYBRID REGIME AND RULE OF LAW - Mišić , Marica (Glasnik Advokatske komore Vojvodine, 2022)
The past and ongoing political affairs linked to pandemic particularly in Serbia (which fits the concept of hybrid regime) raised polemic among some lawyers whether the president’s declaration of state of emergency was constitutional or not. This motivates to make Kelsen – Schmitt debate about who ought to be the Guardian of the Constitution alive and draw some parаllels with contemporary hybrid regimes. Some of the problems arisen in hybrid regimes are in relation to the rule of law, the role of the parliament and the constitution. Most contemporary constitutions are based on the rule of law which is exercised through pluralism, free and fair elections, constitutional guarantees of human and minority rights, separation of powers, independent judiciary and obedience to the constitution and the law. Using the example of Serbia, we may see that the rule of law and role of parliament as the bearer of constituent and legislative authority are endangered by potential dictatorship in hybrid regimes.